Information Overload in Monopsony Markets - Stefano Ficco (Tinbergen Institute, 2004)
I consider a situation in which heterogenous senders (applicants) compete in order to be selected by one receiver (employer). Productivity is private information to the senders, and the receiver processes imperfect signals (applications) to screen among applicants. The information-processing technology is imperfect: the accuracy of each signal in predicting the unknown productivity decreases with the total number of signals processed. I show that, for a sufficiently large market, information overload occurs as there exist equilibria in which too many people apply and the receiver neglects some applications. For any information-processing technology level, information overload equilibria emerge when the cost of sending applications is low relatively to the existing technology level. The magnitude of information overload is bounded and it is larger if the receiver cannot neglect applications. As a result, an overloaded market in which the receiver has to process all applications is less efficient than an overloaded market where neglecting excessive information is an option.
Keywords: C72; D82; J42; 330; Imperfect information-processing technology; quality and quantity of information; information overload; Unvollkommene Information; Informationswert; Monopson; Informationsökonomik; Theorie